Development and Usability of an Advance Care Planning Website (My Voice) to Empower Patients With Heart Failure and Their Caregivers: Mixed Methods Study - Chetna Malhotra; Alethea Yee; Chandrika Ramakrishnan; Sanam Naraindas Kaurani; Ivy Chua; Joshua R Lakin; David Sim; Iswaree Balakrishnan; Vera Goh Jin Ling; Huang Weiliang; Lee Fong Ling; Kathryn I Pollak (JMIR Aging)
Abstract BackgroundWeb-based advance care planning (ACP) interventions offer a promising solution to improve ACP engagement, but none are specifically designed to meet the needs of patients with heart failure and their caregivers. ObjectiveWe aimed to develop and assess the usability and acceptability of a web-based ACP decision aid called “My Voice,” which is tailored for patients with heart failure and their caregivers. MethodsThis study’s team and advisory board codeveloped the content for both patient and caregiver modules in “My Voice.” Using a mixed methods approach, we iteratively tested usability and acceptability, incorporating feedback from patients, caregivers, and health care professionals (HCPs). ResultsWe interviewed 30 participants (11 patients, 9 caregivers, and 10 HCPs). Participants found the website easy to navigate, with simple and clear content facilitating communication of patients’ values and goals. They also appreciated that it allowed them to revisit their care goals periodically. The average System Usability Scale score was 74 (SD 14.8; range: 42.5-95), indicating good usability. Over 80% (8/11) of patients and 87% (7/8) of caregivers rated the website’s acceptability as good or excellent. Additionally, 70% (7/10) of HCPs strongly agreed or agreed with 11 of the 15 items testing the website’s acceptability. Conclusions“My Voice” shows promise as a tool for patients with heart failure to initiate and revisit ACP conversations with HCPs and caregivers. We will evaluate its efficacy in improving patient and caregiver outcomes in a randomized controlled trial.